PENGARUH INOVASI TEKNOLOGI TERHADAP KEPUASAN PENGGUNA DAN KINERJA PEMASARAN LELANG ONLINE: STUDI LITERATUR PADA PLATFORM LELANG DJKN - Agung Nugroho, Erwin Hanggoro; Welsa, Henny; Fadillah, Muinah (JURNAL ILMIAH EDUNOMIKA, 2024)
The auction sector has transformed with digital advancements, leading to the utilization of online platforms such as lelang.go.id, which is managed by the Directorate General of State Assets (DJKN) in Indonesia. This literature analysis seeks to examine the impact of technological innovation on user satisfaction and marketing performance of online auctions, specifically on the lelang.go.id platform. This study utilizes the Technology Acceptance Model (TAM) as the main theoretical framework and integrates the notion of perceived risk to investigate the impact of technical innovation on user perception, satisfaction, and marketing performance of online auctions. The findings from this literature review offer insights for DJKN and relevant stakeholders to improve the effectiveness of the lelang.go.id platform and enhance the user experience in online auctions.